The Financial Cost of a Criminal Conviction: Context and Consequences - Pleggenkuhle, Breanne (Criminal justice and behavior, 2018)
Growing fiscal concerns for criminal justice agencies and punitive ideological shifts have increased the financial consequences of a conviction. The growth in legal financial obligations (LFOs), such as fees, fines, and restitution resultant from conviction has important implications for offender reentry, particularly offender reintegration and opportunities for social advancement. Utilizing data culled from in-depth qualitative interviews with a sample of persons under correctional supervision, the current research documents the nature and prevalence of LFOs for an offending population and explores how they affect post-conviction experiences. The results indicate a majority of ex-offenders experience some form of LFO including fines, supervision costs, and child-support-related fees. Overall, LFOs diminished positive opportunities for offenders by compounding precarious financial states, limiting opportunities for upward social movement, and weakening positive cognitive change. As research consistently identifies primarily adverse consequences from LFOs, policy implications are explored to mitigate negative individual and social outcomes for offenders.